2021
DOI: 10.1590/1809-4430-eng.agric.v41n3p330-337/2021
|View full text |Cite
|
Sign up to set email alerts
|

HYDROGEL AND WATER REGIMES IN THE CHLOROPHYLL- A FLUORESCENCE AND GROWTH OF Campomanesia xanthocarpa SEEDLINGS

Abstract: Water availability is one of the most important factors for the growth of tree seedlings in forestry-related regions. We hypothesized that under different water regimes, a waterretaining polymer (hydrogel) can positively contribute to chlorophyll-a fluorescence and growth in Campomanesia xanthocarpa (Mart.) O. Berg. Four water retention capacities (WRC) were evaluated: 25%, 50%, 75%, and 100%, depending on the presence or absence of hydrogel at the substrate. The lowest WRCs, particularly those under 25% witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In case of water deficit, similar findings of decreased chlorophyll content under lower water availability have been reported in seedlings of several tree species (Santos et al, 2021;Zuazo et al, 2021). SA application, Ribeiro et al (2020) observed increase in chlorophyll content with exogenous application of SA, which favored higher photochemical yields, results similar to those observed in this study with S. terebinthifolia.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In case of water deficit, similar findings of decreased chlorophyll content under lower water availability have been reported in seedlings of several tree species (Santos et al, 2021;Zuazo et al, 2021). SA application, Ribeiro et al (2020) observed increase in chlorophyll content with exogenous application of SA, which favored higher photochemical yields, results similar to those observed in this study with S. terebinthifolia.…”
Section: Resultssupporting
confidence: 90%
“…Since these pigments are responsible for light interception and electron transfer excitation processes, their degradation decreased the photochemical activity of PSII (F v /F m ). The decreased PSII activity leads to increased excitation energy, resulting in excessive energy, ROS production, and lipid peroxidation (Santos et al, 2021;Zhao et al, 2021), thus inhibiting NADPH oxidation and electron transfer to the reaction centers (Xiong et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same responses for LA were observed in seedlings of Schinus terebinthifolia Raddi (Beltramin et al, 2020), Cedrela odorata L. (Silva et al, 2021), and Campomanesia xanthocarpa O. Berg. (Santos et al, 2021), where these species had reduction in LA under low water availability.…”
Section: Discussionmentioning
confidence: 97%